TRZY TRANSFORMACJE W PROCEDURZE CYWILNEJ W POLSCE W XX WIEKU. WZORCE ROZWIĄZAŃ - Stawarska-Rippel, Anna (Zeszyty Prawnicze, 2016)
THREE TRANSFORMATIONS OF CIVIL PROCEEDINGS IN POLAND IN THE 20TH CENTURY. THE LEGAL PATTERNS Summary Poland’s history over the last century was an eventful period of political, state and legal change. There were three transformations of judicial law due to changing political circumstances in twentieth century Poland. The first transformation occurred when independence was gained in 1918. At that point in Poland five different legal system were in force. The decision to temporarily keep the law of the occupying powers until the new Polish legal system was created was taken by the Polish authorities. The work on Polish civil procedure began in November 1919. Using the comparative method all modern legal answers within European civil procedures, which equated with Polish Law, were drafted in the Polish Code of Civil Procedure. The second transformation in Polish judicial law began after World War II, when Poland found itself under the political influenceof the USSR. Formal maintenance of the law of the Second Republic of Poland was decided on in People’s Poland. The legal system of the interwar Poland, including the Code of Civil Procedure (1930), did not square with the principles of the new state system. Code of Civil Procedure (1930) had been „adapted“ to contemporary governance, plitical and ideological so that it would mirror as much as possible the Soviet model. The new Code of Civil Procedure that was adopted during November 1964 retained its binding force so far. However when the third transformation came about soon after 1989, the existing system of law was revised to eliminate the rules and principles characteristic of the socialist legal system. Amendments of the Code of Civil Procedure (1964) have increased the adversarial aspect of civil proceedings. The possibility of the court to order the investigations during the civil procedure was eliminated, but the possibility of the court to obtain evidence ex officio was kept which is intended to guarantee the implementation of the principles of truth, in legal sense and not in the ideological sense.